2016
DOI: 10.1039/c6ra17241e
|View full text |Cite
|
Sign up to set email alerts
|

Highly coplanar bis(thiazol-2-yl)-diketopyrrolopyrrole based donor–acceptor copolymers for ambipolar field effect transistors

Abstract: Highly coplanar bis(thiazol-2-yl)-diketopyrrolopyrrole based donor–acceptor copolymers were synthesized and their field-effect transistors exhibited ambipolar charge carrier transporting performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 74 publications
4
17
0
Order By: Relevance
“…Thieno[3,2‐ b ]thiophene‐flanked DPP‐based copolymer P9 also exhibited higher mobility of 0.205 cm 2 V −1 s −1 , than 0.038 cm 2 V −1 s −1 of P10 in the same device configuration . Especially, thiazole‐flanked DPP‐based copolymers, P11 and P12, both afforded higher hole and electron mobilities than those of P13 and P14, respectively . Thin film microstructure investigations indicated that these DTE‐based copolymers all formed more ordered thin films than their respective DSE‐based copolymers.…”
Section: Types Of Aryl Groups and Dae‐based Polymer Semicondcutorssupporting
confidence: 75%
See 1 more Smart Citation
“…Thieno[3,2‐ b ]thiophene‐flanked DPP‐based copolymer P9 also exhibited higher mobility of 0.205 cm 2 V −1 s −1 , than 0.038 cm 2 V −1 s −1 of P10 in the same device configuration . Especially, thiazole‐flanked DPP‐based copolymers, P11 and P12, both afforded higher hole and electron mobilities than those of P13 and P14, respectively . Thin film microstructure investigations indicated that these DTE‐based copolymers all formed more ordered thin films than their respective DSE‐based copolymers.…”
Section: Types Of Aryl Groups and Dae‐based Polymer Semicondcutorssupporting
confidence: 75%
“…DAE are a kind of π ‐extended vinyl‐bridged biaryl building blocks, in which the aryl groups could be the same, or different (Fig. ) . Some representative DAE units 1 − 15 are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…[21,27] After that, Majumdar et al prepared polymers spin valve with LSMO/P3HT/Co structure, and analyzed that P3HT and LSMO electrodes occurred certain chemical interaction leading to a spin-selective tunneling interface. [49][50][51][52][53][54] In the D−A structure polymers, it is favorable for intramolecular charge transfer, resulting in low band gap, efficient carrier injection, and easy D−A interaction. [43][44][45] In addition, some π-conjugated polymeric materials like poly(3-hexylthiophene) (P3HT), [28,46] poly(2,5-dioctyloxy-p-phenylenevinylene), [47] and P(NDI2OD-T2) [48] were also applied successfully in the OSV devices.…”
Section: Introductionmentioning
confidence: 99%
“…Although some research results have been achieved as mentioned above, preferential polymer structures for organic spintronics are less reached, and the subject is very important for future polymers spintronic applications. In recent years, donor−acceptor (D−A)‐conjugated polymers have attracted widespread attention and are used to prepare highly efficient organic photovoltaics and organic field effect transistors (OFETs) . In the D−A structure polymers, it is favorable for intramolecular charge transfer, resulting in low band gap, efficient carrier injection, and easy D−A interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the optical band gaps and the electrochemical band gaps of these compounds are 0.26-0.40 eV within the acceptable experimental error range according to the literature. 22…”
Section: Electrochemical Propertiesmentioning
confidence: 99%